Dietary methionine requirement of pre‐adult blunt snout bream, (Megalobrama amblycephala Yih, 1955). (27th June 2016) - Liang, H.‐L.; Ren, M.‐C.; Habte‐Tsion, H.‐M.; Mi, H.‐F.; Ge, X.‐P.; Xie, J.; Xi, B.‐W.; Zhou, Q.‐L.; Miao, L.‐H.
Summary: A nine‐week feeding trial was conducted to test the hypothesis that an adequate methionine diet might improve growth, feed utilization, body composition and physiology, and biochemical parameters in pre‐adult blunt snout bream Megalobrama amblycephala, whereas a methionine deficiency might have adverse effects on these parameters. Six isonitrogenous and isoenergetics semi‐purified diets (33.0% crude protein, 7.0% crude lipid) were formulated to contain graded methionine levels (0.39–1.54% of dry weight) at 0.25% increments replaced by equal proportions of glycine. Results show that the survival rate (SR) was not significantly affected by the dietary methionine level. Final weight (FW), feed efficiency ratios (FER), weight gain (WG), and specific growth rate (SGR) increased with increasing dietary methionine levels up to 1.00% and then showed a declining trend. Using quadratic regression analysis of FER and SGR, the dietary methionine requirement was estimated to be 0.74% (2.24% of dietary protein) and 0.76% of the diet (2.30% of dietary protein), respectively. Fish fed the 0.39% methionine diet showed significantly lower whole body protein content compared to those fed with 0.85, 1.00 and 1.24% methionine diets (P   <   0.05). Whole body moisture, lipid, and ash contents in pre‐adult adult blunt snout bream were not significantly affected. The urea content in fish fed the 0.85% methionine diet was significantly higher than those of fish fed a 0.39, 0.56, 1.24, 1.54% methionine diet (P   <   0.05), but not significantly different in fish fed the 1.00% methionine diet (P  > 0.05 ). No significant differences were found in other indexes such as the hepatosomatic index (HSI), viscerosomatic index (VSI), condition factor (CF), albumin (ALB), total protein (TP), alanine aminotransferase (ALT), and spartate transaminase (AST) (P  > 0.05 ). Most important, the optimal dietary methionine level of pre‐adult blunt snout bream should be 0.74–0.76% of the diet (2.24–2.30% of dietary protein).